Pola Makan dan Dampaknya Terhadap Kondisi Psikologis dan Spiritualitas - Olvia Nursaadah; Abdul Wasik (Syifa al-Qulub, 2019)
This research is based on the background that dietary habit does not only have an impact on physical health, but also effects non-physical conditions. This study aims to know  the impact of dietary habit on non-physical conditions, namely psychological & spirituality, on TQN practicing santri in Suryalaya Islamic Boarding School and for non-practicing tarekat students. The research method used is a mixed method with explanatory sequential strategies, taking and processing quantitative data first then deepened through qualitative interviews. The results of this study indicate that the dietary habit applied by the TQN practicing santri in the Suryalaya Islamic Boarding School is higher in the Sufi dietary pattern applied, while the dietary habit adopted by non TQN non-practicing students is relatively more balanced between the modern diet and Sufi diet. The impact of the diet applied by the TQN practicing santri on psychological and spiritual conditions is 2% and 6.7%. While the impact of dietary habit applied by non-practicing TQN students on psychological and spiritual conditions was 4.6% and 22.6%. The conclusion of this study is that the impact of diet on psychological and spiritual conditions in non-practicing TQN students has an impact of 4.6% & 22.6%, the qualitative results explain the value of alturism and negative emotions that affect psychological and spirituality conditions of diet. While the impact of the diet on psychological and spirituality conditions in the TQN practicing santri has an impact of 6.7% & 2%, the qualitative results explain the value of alturism and positive emotions that most influence the psychological & spirituality conditions of the diet.